Intervening for Democracy: The Threat or Use of Force and Crisis in The Gambia - Jones, Andrew (Comparative and International Law Journal of Southern Africa, 2020)
The recent constitutional crisis in the West African state of the Republic of The Gambia saw the incumbent president of the state refuse to relinquish power after he was defeated in a democratic election. While political means were ultimately successful, the early response to the crisis involved the threat of force, which was held over the state throughout the situation and was ultimately carried out by the involved nations. Despite the lack of bloodshed and actual conflict, this resort to the threat and use of force was not in keeping with the accepted prohibitions contained in the United Nations Charter system and international law. This article seeks to outline how the international response to the crisis in The Gambia was a breach of international law in an attempt to impose the will of other states upon the internal political workings of another under the moral justification of the defence of democracy. Further, it will show that the prohibition of the threat or use of force established by the UN Charter system does not make room for force to stand as a stick with which to guarantee democratic freedoms.